Strategi Ritel Lokal dalam Menjamin Keaslian Produk dan Membangun Kepercayaan Konsumen: Belia Cosmetic Surabaya: indonesia - Karin Devia Melawati; Muchammad Saifuddin (Program Sarjana Terapan Universitas Islam Indonesia, 2025)
The growth of the cosmetics industry in Indonesia presents challenges in the form of increasing circulation of counterfeit products that can harm consumers and reduce trust in retailers. For local retailers, the ability to guarantee product authenticity is an important factor in building retailer trust. This study aims to explore the strategies of Belia Cosmetic Surabaya, as a local cosmetic retailer, in ensuring product authenticity and building consumer trust. The research approach uses a descriptive qualitative method with data collection techniques including semi-structured interviews with supervisors and consumers, as well as digital observation of Belia Cosmetic's social media activities. Data analysis follows the Miles and Huberman model through the processes of reduction, presentation, and conclusion drawing. The research results show that Belia Cosmetic implements four main strategies: (1) selection of official suppliers and supply chain control, (2) transparency of information and education about product authenticity, (3) a positive shopping experience through service, cleanliness, and store layout, and (4) leveraging social proof through customer reviews and promotional events. These strategies have been proven to build consumer trust and strengthen perceptions of product quality and authenticity. These findings provide important implications for local retailers in designing marketing strategies that focus on product authenticity and building consumer trust.